MSC Malaysia Cyebrcities and Cybercentres, A Home For Knowledgr Building - New Straits Times, (2008)
In building leadership in the information ange and tranforming Malaysia into the preferred global ICT hub MDeC has been focusing its efforts to make MSC Malaysia the world's best environment in which to harness the full potential of technology. An integral part of the blueprint is the establishment of MSC Malaysia Cybercities and Cybercenters across the nation.